2021
DOI: 10.1177/07482337211019593
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment of occupational exposure to heavy metals in a steel casting unit of a steelmaking plant using Monte–Carlo simulation technique

Abstract: The present work aimed to evaluate the health risks of occupational exposure to heavy metals in a steel casting unit of a steel plant. To determine occupational exposure to heavy metals, personal air samples were taken from the workers’ breathing zones using the National Institute for Occupational Safety and Health method. Noncancer and cancer risks due to the measured metals were calculated according to the United States Environmental Protection Agency procedures. The results indicated that the noncancer risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…In the U.S., Clewell et al ( 54 ) described the process of the PBPK model development and highlighted issues related to the specification of model structure and parameters, model evaluation, and consideration of uncertainty in environmental and occupational risk assessment. Monte Carlo simulation was carried out to assess health risk of occupational exposure to heavy metals in a steel casting unit of a steelmaking plant in Iran ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S., Clewell et al ( 54 ) described the process of the PBPK model development and highlighted issues related to the specification of model structure and parameters, model evaluation, and consideration of uncertainty in environmental and occupational risk assessment. Monte Carlo simulation was carried out to assess health risk of occupational exposure to heavy metals in a steel casting unit of a steelmaking plant in Iran ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Monte Carlo simulation method is a very effective method for the human health risk assessment of environmental contaminants. Dehghani et al [17] adopted the Monte Carlo simulation technique to assess the health risks of heavy metal exposure in a steel plant, and found that further improved control measures should be proposed for reducing the occupational exposure levels. In addition, quantitative health risk analysis based on the Monte Carlo simulation can provide an important scientific basis for evaluating potential human risk assessment [15,18].…”
Section: Introductionmentioning
confidence: 99%
“…Probabilistic methods can reduce the estimation bias caused by uncertainty and obtain more accurate evaluation results [24]. The Monte Carlo simulation (MCS) is an effective probabilistic evaluation method that not only quantifies the uncertainty in the risk assessment but also identifies the degree of influence of the exposure pathways and parameters on the risk, and has been increasingly applied to the risk assessment of HMs [25,26]. Therefore, we attempt to take advantage of this by using a combination of the HRA and the MCS to assess the health risk in this study.…”
Section: Introductionmentioning
confidence: 99%